Comparative study on the chemical and rheological properties of elastomer-based and resin-based HVMAs. (August 2022) - Zhou, Zhengfeng; Yu, Xiaotao; Yuan, Linxin; Yan, Chuanqi
Highlights: Resin HVMA contains crystallization structure and exhibits a large modulus. Elastomer HVMA has three-dimensional elastic network structure. Resin HVMA may be more suitable for the wearing layer structure with less strain. Both HVMA can significantly improve the plain asphalt's rheological properties. Abstract: High viscosity modified asphalt (HVMA) is a complex material whose chemical ingredients and rheological properties determine its mixture performance. The chemical composition and modification mechanism of HVMA were examined using gel permeation chromatography (GPC), differential scanning calorimetry (DSC), transmission electron microscopy (TEM), and attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR). Dynamic mechanical analysis and multiple stress creep and recovery (MSCR) test were performed using DHR-3 to analyze the asphalt binder at the linear/nonlinear viscoelasticity level. Moreover, the high-temperature performance of the mixture was examined using a mixture wheel tracking test. The results show that the elastomer modifier is a polyolefin-based block copolymer whose strength and toughness are determined by molecular crosslinking, whereas the resin modifier has a uniform saturated long-chain structure that tends to crystallize below 110 °C. Above this temperature, the crystallized structure rapidly diminishes and renders good workability. The crystallized structure of the resin modifier is more efficient in enhancing the high-temperature performance of asphalt than that of the crosslinked elastomer. However, it is also more stress sensitive. The elastomer HVMA exhibits slightly lower high-temperature performance than the resin HVMA. Resin HVMA has the advantages of energy savings and environmental protection compared with elastomer HVMA based on the Sustainable Development Goals. Nevertheless, both HVMA materials are significantly better than plain asphalt.